PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN TEKNIK ELEKTRONIKA DASAR KELAS X JURUSAN TEKNIK ELEKTRONIKA DI SMK NEGERI 1 SUMATERA BARAT - Risqi Fajril; Almasri Almasri; Andris Syukur (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
AbstractThis research is aimed to know the difference between Team Games Tournament model  and Cooperative model in learning ouput in Teknik Elektronika Dasar for grade X Electronic Engineering of SMKN 1 Sumatera Barat on entire semester, academic year 2014/2015. This type of research is quasi experimental. Participant were slected by non-probability sampling technique with purposive sampling. 24 students from Class X TAV, which served as a controling class, used Cooperative model. 28 students from Class X Mechatronic, which served as experimental class, used student cooperative type Team Games Tournament model. Data is collected from the final test then was analyzed for homogeneity testing, normality and hypothesis testing. The result indicates that experimental class has mean 79,29, while controlling class has mean 70,17. The result of hypothessis testing on significant level α=0,05 is 4,583 > 1,676 and the percentage effect 12.997 %. Since the tcount is higher than the t table, then Ho is rejected and Ha is accepted. It can be inferred that Team Games Tournament model is better than Cooperative  model. Keywords: Team Games Tournament model, Cooperative  model, Learning outcomes